PENGARUH JENIS AKTIVATOR KIMIA TERHADAP DENSITAS DAN KAPASITANSI SPESIFIK ELEKTRODA KARBON AKTIF DARI SERBUK GERGAJI KAYU KARET - E. Taer; A. Ira; Sugianto Sugianto; R. Taslim (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2016)
Supercapacitor electrodes from rubber wood sawdust based on various of chemichal activation agent of KOH, NaOH and ZnCl2 by a concentration of 0.4 M has been analyzed. The production of activated carbon electrodes was started with the process of pre-carbonization and continued with milling process. Sampel were carbonized at temperature 600 oC and followed by physical activation process in CO2 gas atmosphere at the constant temperature of 900 oC. Measurement data of mass, diameter and thickness were collected at a every step such as: (i) before carbonization, (ii) after carbonization and (iii) after physical activation processed to obtained the density values. The density of activated carbon electrodes with different of  activating agent of  KOH, NaOH and ZnCl2 were 0.813 g/cm3, 0.737 g/cm3 and 0.870 g/cm3, respectively. The electrochemical properties of activated carbon electrodes were analyzed by using cyclic voltammetry (CV) method for various of activating agent of KOH, NaOH and ZnCl2 were 60.650 F/g, 59.619 F/g and 103.570 F/g, respectively. As a conclution, the activated carbon with ZnCl2 activating agent  has the highest  of density and spesific capacitance value. As a addition the termogravimetri analysis given the information in the produce of the heating process.Keywords: Sawdust Wood Rubber, Specific Capacitance, Density, Chemical Activation.